Production of a microfiltration membrane from acrylic fiber (AF) and low-density polyethylene (LDPE) shrink film wastes - (:unkn) unknown (SPRINGER, 2021)
The main purpose of this study is the production of a nanofiber membrane from industrial wastes by using the electrospinning technique and determination of its filtration performance. Industrial wastes such as low-density polyethylene shrink film packaging (LDPEWs) and acrylic fiber (AFWs) were used as raw materials to reduce the cost of membrane production as an alternative to expensive commercial membranes. Experiments were carried out to find suitable solvents in order to solve the LDPEWs and AFWs before the electrospinning process, and optimum mixing ratios were determined. After determining the optimum solvent mixture of LDPEWs-AFWs and their proportions, nanofibers were produced by electrospinning process on the surface polypropylene (PP) nonwoven support layer, and their structures were examined. Under optimum conditions, a hydrophilic electrospun membrane with 0.478 mu m pore size (MF-microfiltration), 230 nm nanofiber diameter and 20 degrees liquid-membrane contact angle were obtained under optimum conditions, and a membrane module was created to use in wastewater filtration experiments. In order to determine filtration performance of the produced membrane, permeability and wastewater filtration tests were carried out by using real wastewater, and high pollutant removal rates (> 95%) were obtained in our experiments. Graphic abstract
Keywords: Acrylic; Membrane; Nylon; Polyethylene; Waste